Killer-cell immunoglobulin-like receptor expression on lymphocyte subsets in multiple sclerosis patients treated with interferon-β: evaluation as biomarkers for clinical response - García-León, Juan Antonio; López-Gómez, Carlos; Orpez-Zafra, Teresa; Reyes-Garrido, Virginia; Marín Bañasco, Carmen; Oliver-Martos, Begoña; Fernández-Fernández, Óscar; Leyva-Fernández, Laura (Springer Link, 2014)
Background: Both the adaptative and the innate immune systems interplay in multiple sclerosis (MS) pathogeny. Killer-cell immunoglobulin-like receptors (KIRs) are key regulators of the immune response, with activating and inhibitory isoforms. Objective: In this study we analysed whether the expression of KIR isoforms is implicated in MS pathogenesis and in the therapeutic response to interferon (IFN)-β. Methods: Peripheral blood samples were collected from 78 IFN-β-treated MS patients and 46 healthy controls (HC). KIR expression was evaluated by flow cytometry on natural killer (NK) and T cells. Results: The expression of KIRs on NK cells and T lymphocytes did not differ between MS patients and HC. IFN-β therapy decreased the expression of KIR2DL1/2DS1 and increased that of KIR2DL2/3 on NK cells. This therapy also reduced KIR2DL1/2DS1, KIR2DL2/2DL3 and KIR3DL2 expression on CD8(+) T cells. The baseline evaluation of the percentage of circulating CD16(+) NK cells was predictive of the clinical response to IFN-β; however, response to this therapy did not appear related to KIR expression. Conclusions: This study shows that expression of KIR isoforms on NK and T lymphocytes correlated in different ways with IFN-β therapy, suggesting that KIR dynamics may be associated with the pathways involved in the mechanisms of action of IFN-β.
Keywords: Esclerosis múltiple; biomarker; multiple sclerosis; Killer-cell immunoglobulin-like receptor